Corporate Social Responsibility Commitment and Environmental Disclosures Quality: Study of the French Context - Khelil- Rhouma, Zouhaira; Hamed- Sidhom, Mounira (Asian Journal of Empirical Research, 2019)
The aim of this study is to examine the effect of firms’ corporate social responsibility commitment (CSR) on the quality of their environmental reporting. The proactive approach of the legitimacy theory is retained to formulate our expectations. We develop a multidimensional content analysis index used to apprehend environmental disclosure faithfulness dimensions. The variance analysis is applied to these indicators classified according to the variables of CSR commitment for a sample of French industrial firms listed in the SBF120 index. The study confirms the proactive approach of legitimacy. It provides empirical evidence in the French context that firms use environmental reporting for accountability with a substantial legitimation strategy. Indeed, most CSR committed sampled firms disclose in their annual reports more comprehensive mandatory environmental information and more abundant and precise voluntary information than others. They also tend to introduce more statements to justify the credibility of their disclosures than less committed firms.